2019
DOI: 10.1007/s13197-019-03689-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of volatile compositions of 15 different varieties of Chinese jujube (Ziziphus jujuba Mill.)

Abstract: Jujube (Ziziphus jujuba Mill.) extract has been commonly used as a flavoring ingredient due to its unique aroma. In this study, solid phase micro extraction method was used to extract the volatile compounds in fresh jujube, with the aid of GC-MS for further chemical separation and identification. As a result, 33 volatile compounds, including aldehydes, alcohols, acids, ketones and esters, were identified. Among them, hexanal (276.5-1314 lg/100 g FW), (E)-2-hexanal, (145.1-1876 lg/100 g FW), nonanal (188.2-1047… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Additionally, some information on the volatile compounds was lost during the statistical re-modeling. As shown in the loading plots (Figure 6B and Figure 7B), the length of the arrow reflects the extent of information loss, the shorter the arrow, the more information lost [20]. For example, linalool oxide and 5-methyfurfural suffered the most with the loss of their information of DZ, but in JS, dimethyl sulfide loss was the highest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some information on the volatile compounds was lost during the statistical re-modeling. As shown in the loading plots (Figure 6B and Figure 7B), the length of the arrow reflects the extent of information loss, the shorter the arrow, the more information lost [20]. For example, linalool oxide and 5-methyfurfural suffered the most with the loss of their information of DZ, but in JS, dimethyl sulfide loss was the highest.…”
Section: Resultsmentioning
confidence: 99%
“…Aroma profiles are important characteristics to evaluate the quality of fruits. Several studies have reported that the volatile compounds of jujube fruits are affected by many factors, such as growth period [14], extraction methods [15], the load [16], and processing methods [17,18,19,20]. However, few reports have been associated with changes in volatile compounds of jujube fruits during cold storage, which should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…( 2015 ) used this method to detect the volatile components in jujube fruit, finding that there were a total of 18 volatile components detected, and the aldehydes and acids such as hexanal, (E)‐2‐hexanal, benzaldehyde, hexanoic acid, and decanoic acid accounted for 95%. Wang, et al ( 2019 ) also used this method to detect the volatile components in jujube fruit, finding that there was significant difference in volatile components among different varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, heterocyclic compounds such as 5-hydroxymethyl-2-furaldehyde were detected before and after fermentation, probably due to the heating of sugars and the production of some new substances [ 55 ]. Hexanal with a unique herbal flavor is the most reducing volatile compound and can reduce the strong plant odor of the beverage [ 56 ].…”
Section: Discussionmentioning
confidence: 99%